Design of Two-Regional Flexible-Route Bus Systems considering Interregional Demands - Siqing Wang; Jian Wang; Lang Song; Zhipeng Niu; Xiaowei Hu (Journal of Advanced Transportation)
The flexible-route bus system is a type of dynamic public transit service. Routes and timetables are not fixed during the operation process, and driving routes are planned according to passengers’ reservation needs. This study develops a model that considers inter-regional travel demands. The optimal network layout is determined by minimizing an objective function that comprises operator and user costs. Then, two cases with and without loop-line buses are analyzed. In the case of the joint optimal solution, the parameter values of region side width, region angle, and cost components are compared. Results indicate that regional flexible transit is suitable for operation in areas with low demand density. Within certain ranges, increases in vehicle capacity and in the number of circle layers result in additional average total costs. Furthermore, adopting a mode with a loop is better when numerous inter-regional demands exist. The findings derived from numerical and sensitivity analyses can be used as planning guides for designing flexible-route bus systems.